Adrenal Gland Incidentalomas: Case reports - Rijhsinghani, Archana N (Annals of Pathology and Laboratory Medicine, 2023)
Adrenal lesions are serendipitously discovered in upto 5% of cross-sectional examinations performed for other purposes and are hence labeled incidentalomas. Here is the presentation of two cases, one of which is myelolipoma, second common cause of adrenal tumor and other is a rare bronchogenic cyst.